ATTITUDE AND ABILITY TO OVERCOME BARRIERS IN PRACTICING OF PHYSICAL EXERCISE AMONG ACADEMY STAFF IN FACULTY OF MEDICINE, UITM - Rozali, Siti Nur Shakirah Mohd; Anuar, Fadzlin Najwa; Rahman, Che Syahida Silmi Che Abdul; Rahazi, Nurul Amirah Hannah; Adnan, Ahmad Aiman Mohd; Al-Kubaisy, Waqar; Mustafah, Nadia Mohd (LIFE: International Journal of Health and Life-Sciences, 2015)
Several studies had highlighted the importance of exercise as a conservative treatment in medical world. The highly increased of the burden of disease especially the Non-communicable disease contributed to the increasing of the needs toward achieving optimum exercise benefits. It is evident that medical practitioners plays important role to implement and promote exercise among general population. Identifying the attitude of academic staff towards physical exercise was crucial in this aspect. Objectives: To determine the attitude and ability in overcoming exercise barrier in performing physical exercise in addition to identify the correlation between them among academic staff with and without medical graduated Methodology: A cross sectional study had been conducted, from January- September 2015, in two UiTM campuses (Sungai Buloh and Selayang). Sample of 155 academic staff consist of both medical and non-medical graduate was collected. Each participant was given well-structured questionnaire to be answered. Questionnaires contain two domains; the first one consists of six items reflecting either positive (2) or negative (4) attitude toward exercise. The second domain consists of seven items reflecting the ability in overcoming exercise barrier. Five-point-scoring: (1) very much overcome - (5) not at all, were given for each item. In addition, the questionnaire also contains information about the socio-demographic details of each participant. Result: The majority (95.5%) having good attitude towards physical exercise. No significant difference in the rate of good attitude between medical (95.7%) and non-medical (93.3%) graduate. There is no correlation between the general attitudes towards exercise with the ability to overcome exercise barriers. Significantly, male shows higher rate (77.4%) of ability of overcoming exercise barrier compare to woman (43.3%). No significant association between other socio-demographic characteristic (age, race, marital status) with neither general attitude towards exercise nor ability in overcoming exercise barrier. Conclusion: The majority of academic staff having good attitude. No significant difference between Medical and non-Medical graduate in terms of attitude and ability of overcoming exercise. No significant association between various socio-demographic profile and attitude towards exercise except for gender.